2023
DOI: 10.7554/elife.79742
|View full text |Cite
|
Sign up to set email alerts
|

Associations of genetic and infectious risk factors with coronary heart disease

Abstract: Coronary heart disease (CHD) is one of the most pressing health problems of our time and a major cause of preventable death. CHD results from complex interactions between genetic and environmental factors. Using multiplex serological testing for persistent or frequently recurring infections and genome-wide analysis in a prospective population study, we delineate the respective and combined influences of genetic variation, infections, and low-grade inflammation on the risk of incident CHD. Study participants ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…As in the case of neurological diseases, there is still little evidence to support a role for ectopic colonization by oral bacteria in cardiovascular diseases. Very recently, Hodel et al ( 2023 ) pointed out a positive correlation between the detection of antibodies against the oral pathobiont F. nucleatum and a higher risk of suffering from coronary heart disease. A previous study demonstrated that F. nucleatum can migrate from the oral cavity to arterial plaques (Figuero et al 2011 ).…”
Section: Ectopic Colonization By Oral Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…As in the case of neurological diseases, there is still little evidence to support a role for ectopic colonization by oral bacteria in cardiovascular diseases. Very recently, Hodel et al ( 2023 ) pointed out a positive correlation between the detection of antibodies against the oral pathobiont F. nucleatum and a higher risk of suffering from coronary heart disease. A previous study demonstrated that F. nucleatum can migrate from the oral cavity to arterial plaques (Figuero et al 2011 ).…”
Section: Ectopic Colonization By Oral Bacteriamentioning
confidence: 99%
“…For years, the exact origin and nature of ectopically colonizing oral strains has been an open question in the field. Indeed, most of the studies assessing for ectopic colonization by oral bacteria are based on 16S rRNA gene amplicon sequencing data (Muhlebach et al 2018 , Dinakaran et al 2019 , Chen et al 2020 , 2021 , Yin et al 2021 , Hodel et al 2023 ), thus not allowing for strain-level inference and comparisons. In recent years, several studies have started to tackle this question by analyzing in parallel the microbiome in the saliva as well as from ectopically colonized sites.…”
Section: Ectopically Colonizing Strains: Insights Into Their Origin A...mentioning
confidence: 99%
See 1 more Smart Citation